Investigation method for relationship between weight and stiffness on double skin carbody made of aluminum alloy for railway - Takeshi KAWASAKI (Nihon Kikai Gakkai ronbunshu)
Railway vehicles are required to reduce environmental impact with acceptable riding comfort. For this purpose, it is necessary to satisfy the conflicting issues of weight reduction and maintaining proper stiffness. However, in order to find out acceptable structure, repetitive calculation with finite element analysis is required because of its large and complex structure with thousands of parts. Here, it is required to accelerate analysis and establish a method for solution space. In this report, we propose a method to find out solution space between weight and stiffness on a "double-skin structure" composed of aluminum hollow extrusions for railway. We focused on the first vertical bending modes of the structure as an index of riding comfort and evaluated the equivalent bending stiffness of the structure based on the maximum amount of deflection obtained by static finite element analysis. In order to find out the solution space, we took three steps in the report. First, based on factors that would contribute to considerable bending stiffness extracted based on past research cases and experience, the magnitude of the contribution was quantitatively obtained and extracted using the experimental design method. Next, for the extracted factors, the relationship between the structure mass and the equivalent bending stiffness was formulated. Finally, solution space was obtained by inputting numerical values into the design factors within a practical range using the Monte Carlo method. As a result, it is concluded that proposed method brings solution spaces.